Социология профессии как призвание: Владимир Николаевич Шубкин - Штайнер, Г. (Социология: теория, методы, маркетинг, 2008)
Владимир Николаевич Шубкин (1923 г. р.) — выдающийся советский и российский социолог, внесший неоценимый вклад в становление советской социологии и формирование Новосибирской социологической школы, а так же в развитие методологии применения количественных методов в социологии. Тематика его исследований связана, в частности, с социологией образования, молодежи и профессионального выбора. Ныне — главный научный сотрудник, руководитель группы изучения со знания молодежи сектора социологии образования и молодежи Института социологии Российской академии наук (Москва). Является Заслуженным деятелем науки Российской Федерации, членом Международного комитета по урбанистике, вице-президентом Международного научно-исследовательского комитета по социологии молодежи, членом Президентского совета Профессиональной социологической ассоциации, директором российской национальной части международного проекта “Катастрофическое сознание в современном мире”. Поздравляем Владимира Николаевича с 85-летием и публикуем статью Гельмута Штайнера о нем как о социологе по призванию. The article is devoted to history of Soviet and Russian sociology through the prism of the prominent contemporary sociologist Vladimir Shubkin biography. Author of argue that Shubkin is an inalienable part of Soviet and Russian sociological history. The institutionalization of Russian sociology, as well as that of Western sociology, was initiated on the threshold of 19th – 20th centuries. But since 1928, when Marxism- Le ninism began to assert itself in USSR, this process has come to a halt. Only at the end of 1950s–at the beginning of 1960s both Soviet and Eastern European scientists, on their side, undertook an attempt to develop sociological science in the context of their time. Scientific and political activities of Shubkin are related to Novosibirsk. He became the founder of Novosibirsk school in Soviet sociology. His merely sociological works embrace such major areas, as sociology of young generation, professional orientations, mecha nisms of social reproduction in the fields of education and professional mobility etc. At the beginning of 1970th, Shubkin has revealed for himself the genre of sociological publicism. He yearned for understanding the contradictory and ambiguous history of his heartland on the basis of his own experience, the history of his family, which was affected be repressions like quite a lot of Soviet families, and rereading the sociological considerations of such thinkers, as Tolstoj and Dostojevskij. His humanistic and democratic credo was embodied in Vladimir Shubkin’s collection of essays “Violence and freedom”.